Pancreatic Carcinosarcoma: Case Report of a Rare Type of Pancreatic Neoplasia - Oymaci, Erkan; Argon, Asuman; Coşkun, Ali; Uçar, Ahmet Deniz; Carti, Erdem; Erkan, Nazif; Yildirim, Mehmet (JOP. Journal of the Pancreas, 2013)
Context Carcinosarcoma of the pancreas is a rare entity comprising a small subset of all pancreatic neoplasms. Diagnosis is usually established by immunohistochemical examination of the resected specimen. Prognosis is limited to several months after resection. Case report We review the current literature on this rare type of neoplasia, considering histopathological and clinical features. The pathologic findings revealed areas of both adenocarcinoma and sarcoma of the pancreas. The adenocarcinomatous areas localized to the tumor within the head of the pancreas whereas the sarcomatous areas localized to regions of the intraductal component. Discussion Carcinosarcoma of the pancreas is a rare disease having a dismal prognosis. To our knowledge, this carcinosarcoma is the very rare reported case of a primary pancreatic neoplasm with mixed carcinomatous and sarcomatous components. Image: Solid and cystic areas in a tumor localized in the head of the pancreas.